Diversity of endophytic bacteria Isolated from Leguminous Agroforestry Trees in Western Kenya - Emitaro, William Omuketi (AMB Express, 2024)
Plants have diverse and vast niches colonized by endophytic microorganisms that promote the wellbeing of host plant. These microbes inhabit internal plant tissues with no signs of ill health. Bacterial endophytes from many plants have been isolated and characterized due to their beneficial roles however their diversity in leguminous plants still remain unexploited. Diversity of bacterial endophytes isolated from Sesbania sesban, Leucaena diversifolia and Calliandra calothyrsus was assessed using morphological and molecular characteristics. A total of 27 pure isolates were recovered from C. Calothyrsus, L. diversifolia and S. sesban constituting 44.4%, 33.3% and 22.2% from the leaves, stems and roots respectively. The isolates differentiated into Gram positive and negative with rods and spherical shapes. Analysis of 16S rRNA gene sequences revealed 8 closely related bacterial genera that consisted of Bacillus (33.3%), Staphylococcus (22.2%), Alcaligens (11.1%), Pantoea (11.1%), Xanthomonas,and Sphingomonas (7.4%) each. Others included Acinetobacter, and Pseudomonas at 3.7% each. Bacterial endophytes of genus bacillus were isolated from all the three plants. These results indicate the presence of high diversity of endophytic bacteria associated with the different parts of L. diversifolia, S. sesban and C. salothyrsus growing in western Kenya.
Keywords: Niches; Morphological; Characterization; Molecular; Spherical; Rod shaped